The Proton Pump Inhibitor Non‐Responder: A Clinical Conundrum. Issue 8 (August 2015) - Hussain, Zilla H; Henderson, Emily E; Maradey‐Romerao, Carla; George, Nina; Fass, Ronnie; Lacy, Brian E
Abstract : N/A: Gastroesophageal reflux disease (GERD) is a highly prevalent chronic condition where in stomach contents reflux into the esophagus causing symptoms, esophageal injury, and subsequent complications. Proton pump inhibitors (PPI) remain the mainstay of therapy for acid suppression. Despite their efficacy, significant proportions of GERD patients are either partial or non‐responders to PPI therapy. Patients should be assessed for mechanisms that can lead to PPI failure and may require further evaluation to investigate for alternative causes. This monograph will outline a diagnostic approach to the PPI non‐responder, review mechanisms associated with PPI failure, and discuss therapeutic options for those who fail to respond to PPI therapy.